ANALISA STRUKTUR GEDUNG SEKOLAH DI GROBOGAN - Muhroni, Alim; Wijaya, Tenardhy Aryarama (JURNAL ILMIAH TEKNIK SIPIL, 2025)
Due to the need for educational facilities, schools in Kabupaten Grobogan must expand their student capacity. The construction of a new building is one of the alternatives to meet these needs. To meet the needs of a 3-storey building, the new building must also be designed to withstand earthquake loads with the help of SAP 2000 v20 software. The results of this study found that the amount of Participating Mass Raatio in the school building is greater than 99%, the value of the Spectrum Response comparison with the Equivalent Static on the X axis is 104.52% and on the Y axis is 102.52%. Based on the calculation of the deviation between floors, if an earthquake occurs with the data that has been entered, the building does not collapse and the ratio of columns and beams meets the permitted ratio.